2016
DOI: 10.3747/co.23.3023
|View full text |Cite
|
Sign up to set email alerts
|

Management of Small-Cell Lung Cancer with Radiotherapy—A Pan-Canadian Survey of Radiation Oncologists

Abstract: BackgroundThe management of small-cell lung cancer (sclc) with radiotherapy (rt) varies, with many treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Since then, the radiotherapy doses used in standard fractionation have increased to ∼60–66 Gy and a direct comparison between the higher dose standard-fractionation and the twice-daily schedule was missing. The potential inconvenience of twice-daily administration and the significantly increased rates of transient grade 3 esophagitis were the main concerns that explain why the twice-daily regimen was not universally adopted ( table 1 ) [ 30 , 31 ]. The recent CONVERT phase III trial did not demonstrate superiority of once daily radiotherapy with 66 Gy when compared to the aforementioned twice-daily regimen, with both regimens having very similar toxicity rates [ 29 ].…”
Section: Standard Of Care For Ld-sclcmentioning
confidence: 99%
“…Since then, the radiotherapy doses used in standard fractionation have increased to ∼60–66 Gy and a direct comparison between the higher dose standard-fractionation and the twice-daily schedule was missing. The potential inconvenience of twice-daily administration and the significantly increased rates of transient grade 3 esophagitis were the main concerns that explain why the twice-daily regimen was not universally adopted ( table 1 ) [ 30 , 31 ]. The recent CONVERT phase III trial did not demonstrate superiority of once daily radiotherapy with 66 Gy when compared to the aforementioned twice-daily regimen, with both regimens having very similar toxicity rates [ 29 ].…”
Section: Standard Of Care For Ld-sclcmentioning
confidence: 99%
“…1,[3][4][5][6][7] A variety of radiation therapy dose fractionation regimens are commonly used in CRT for LS-SCLC. 4,5,[8][9][10][11][12][13][14][15] Phase 3 clinical trial data support the use of both hyperfractionated radiation therapy (45 Gy in 30 twice-daily fractions) and high-dose conventionally fractionated radiation therapy (CFRT, 66 Gy in 33 daily fractions); these regimens appear to achieve comparable survival outcomes with similar toxicity profiles. 5,16 Alternatively, hypofractionated radiation therapy (HFRT) using !2.1 Gy per fraction is also practiced in certain parts of the world, with a common regimen being 40 Gy in 15 fractions.…”
Section: Introductionmentioning
confidence: 98%
“…5,16 Alternatively, hypofractionated radiation therapy (HFRT) using !2.1 Gy per fraction is also practiced in certain parts of the world, with a common regimen being 40 Gy in 15 fractions. 15 A phase 2 trial comparing HFRT to hyperfractionated radiation therapy demonstrated similar progression-free survival (PFS) and OS outcomes, although this study had a limited sample size, restricting its power. 17 There is currently no completed randomized clinical trial comparing HFRT to CFRT, yet HFRT remains the preferred radiation therapy schedule in several countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, twice-daily and once-daily radiotherapy regimes have evolved for SCLC side-by-side [55][56][57][58][59][60][61]. SCLC can be treated with daily radiotherapy (to 66 Gy) or with twice-daily treatment (to 45 Gy), both with a relatively favourable 3-year survival rate of ∼40% and similar toxicity rates [62].…”
Section: Radiochemotherapymentioning
confidence: 99%